2021
DOI: 10.1186/s43019-021-00120-4
|View full text |Cite
|
Sign up to set email alerts
|

A characteristic MRI finding to diagnose a partial tear of the medial meniscus posterior root: an ocarina sign

Abstract: Background Diagnosing partial tears of the medial meniscus (MM) posterior root is difficult. The aim of this study was to evaluate diagnostic values involved in conventional magnetic resonance imaging (MRI) features of MM posterior root tears (MMPRTs) and find other MRI-based findings in patients with partial MMPRTs. Methods Eighteen patients who had arthroscopically confirmed partial MMPRTs were included. As a control, 18 patients who underwent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…An MRI evaluation was performed using Achieva 1.5 T (Philips, Amsterdam, the Netherlands) with a knee coil, as previously reported [6]. The MRI‐based MME was defined as the distance from the medial margin of the tibial plateau to the outer border of the MM that crossed the midpoint of the anteroposterior length of the MM.…”
Section: Methodsmentioning
confidence: 99%
“…An MRI evaluation was performed using Achieva 1.5 T (Philips, Amsterdam, the Netherlands) with a knee coil, as previously reported [6]. The MRI‐based MME was defined as the distance from the medial margin of the tibial plateau to the outer border of the MM that crossed the midpoint of the anteroposterior length of the MM.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, untreated MMPRT may lead to rapid osteoarthritis progression in the knee joint’s medial compartment [ 3 , 4 ]. As prior research has indicated that MMPRTs are biomechanically equivalent to total medial meniscectomy [ 5 ], accurate diagnosis and early repair are essential for subsequent treatment [ 6 ]. Several techniques have been introduced for MMPRT repair; transtibial pullout repair is frequently performed, as it does not require posterior portals, whereas trans-osseous drilling may enhance meniscal healing through stem-cell recruitment from the bone marrow [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in medial meniscus posterior root tears (MMPRTs) has been growing. MMPRTs, which are defined as radial tears or avulsion injuries on bony attachments, 1 2 3) result in decreased contact surface and increased peak pressure through a loss of hoop tension due to circumferential fiber disruption. 4 5 6) MMPRTs can result in complications after total meniscectomy, with pathologic loads leading to degenerative arthritis.…”
mentioning
confidence: 99%